DEATH IN THE HOME: DOMESTIC VIOLENCE AGAINST WOMEN IN KHYBER PAKHTUNKHWA - Shah, Mian Mujahid; Alam, Naveed; Hassan, Qudsia; Khan, Sahibdad; Qayum, Iftikhar; Bahadur, Sher; Khalil, Zahid Hussain (Journal of Ayub Medical College Abbottabad, 2012)
Background: Domestic or Interpersonal Violence (IPV) remains a major global problem often resulting in morbidity and mortality. The present study was conducted to determine the scope of deaths related to domestic violence in the Khyber Pakhunkhwa province, Pakistan. Methods: Data were collected on all reported female fatalities due to domestic violence for the years 2009-2011 from the records of the department of Forensic Medicine, Khyber Medical College Peshawar for analysis. Results: A total of 305 deaths were reported, showing an increasing trend of 115 deaths for 2009-10 and 190 deaths for 2010-2011. The majority, 182 (59.7%) belonged to the rural areas and 123 (40.3%) to urban areas of the province. Victims were generally of the younger age groups (17% below age 16 and 42.3% between 17-32 years). Homicide was the manner of death in 293 (96.1%) while the most common causative agent was firearm injury (235, 77.1%). Head and neck injuries were most common (52.6%) followed by the chest and abdomen (31.6%) while multiple sites and extremities accounted for 15.8% of injuries. Conclusion: Young and adult females of KPK province of Pakistan are susceptible to homicidal deaths due to domestic violence, perpetrated through firearm injuries to the head and neck regions. Keywords: Domestic violence, Interpersonal violence, Homicide, Firearm injury, Young females